TEACHER UNDERSTANDING IMPLICATIONS ON THE DIFFERENCES OF ELEMENTARY SCHOOL STUDENTS - Putri, Amartia; Lipiah, Dede; Hidayati, Nurul; Magdalena, Ina (PROGRES PENDIDIKAN, 2021)
Every human being was created by the Creator with all the uniqueness and characteristics or characteristics of each. This is referred to as individual differences (individual differences). Individual differences are differences in abilities and characteristics (cognitive, personality, physical skills, etc.) between students at a certain age level and in each particular group. Through educational practices and activities, we can accommodate the individual differences of students. Likewise, the learning styles of each other are also different. There are visual, auditory, and kinesthetic learning styles. The differences in students have big implications for learning in schools. Therefore, education personnel, especially a teacher, must know and understand the differences in students to design learning with appropriate methods, models, and approaches. If learning is carried out by paying attention to differences in students, then the delivery and acquisition of knowledge can be carried out optimally. Thus, learning objectives can be achieved without having to put pressure on students. In addition, the teacher's understanding of individual differences in students can foster a comfortable feeling for learning at school.